Reconstruction of large sacral defects following tumour resection: A report of two cases. - Cheong, You Wei; Sulaiman, W.A.; Halim, A.S. (Hong Kong Academy of Medicine Press, 2008)
Sacral tumours often present surgical resection and reconstruction challenges. Wide resections result in large sacral defects and neoadjuvant radiotherapy impairs wound healing. The wounds need to be covered with bulky, well-vascularised, healthy tissues. We present 2 cases where large sacral defects were reconstructed following tumour resection. Both defects were reconstructed with inferiorly based, transpelvic, pedicled vertical rectus abdominis myocutaneous flaps. This is a robust flap and carries a well-vascularised muscle bulk and skin paddle. The donor site is distant from the lesion site and is thus unaffected by both the resection and radiotherapy. This is a useful flap for reconstructing large sacral defects.